Thursday
March 30, 2017

Post a New Question

Posted by on .

Solve by elimination method-thanks fro checking my work

2x + 3y= 2 multiply this equation by 2= 4x + 6y = 4

4x-2y = -28



4x + 6y = 4

-4x -2y = -28

8y = 32

y = 4

2x + 3(4) = 2

2x + 12 = 2

2x + 2-12

2x = -10

x = -5

solution = (-5,4)

  • Algebra II-Please check my solution - ,

    you're on the right track but when you tried to subtract the 2 eq you only subtracted the first term, but left the others' signs the same.
    It should look like this:
    4x+6y=4
    -4x+2y=28 now add the two eq together and redo the work you did before. if you have more questions just ask!

  • Algebra II-Please recheck-Please check my solution - ,

    when I wrote the -4x -2y = 28
    I forgot to put the next step which was -4x + 2y = 28
    but isn't the rest of my steps the same still because when I subtracted those they became 8y = 32 and the rest Thanks for responding-I'm not sure if this isn't right still-I think the answer is correct minus the one step I forgot to write

  • Algebra II-Please recheck your correction-Please check my solution - ,

    I think I see where you mistook what I wrote-I'm doing the elimination method and subtracting the equations so the new equations were
    4x + 6y = 4 after I multiplied first equation by 2
    minus 4x -2y = -28 and so the 4x becomes -, the -2y becomes positive and the -28 becomes positive, correct
    Thank you

  • Algebra II-Please check my solution - ,

    You're right. I'm sorry. When I saw the missed step, I stopped looking at the rest of the work. You are correct.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question